Insights on film and TV series analysis in sociology in times of digital media spread - Túlio Rossi (Communication & Society (Formerly Comunicación y Sociedad))
This article aims to combine research agendas on Digital Sociology and the Sociology of cinema, explicitly considering the spread of Serial TV Shows on streaming platforms such as Netflix and HBO-Max. Since the early 2000s, with Web 2.0 allowing a shift in the traffic and consumption of multimedia –music, photos, videos, and animation– on the Internet, the presence of audiovisual content in everyday life has become more intensified than before with cinema and broadcast television. It is argued in this paper that this technological shift changes how societies and individuals relate to electronically mediated images and constitute symbolic and valuation references through social life. However, much of the cultural and imagistic references set in motion in present digital media were established by cinema and television currently in the 20th century, being seen in a naturalized way, although historically produced. This paper reviews Pierre Sorlín’s sociological approach to films as ideological productions, contributing to form historical and social shared ways of conceiving reality, and Sorlin’s methodological guidelines for analyzing films. However, the differences between cinema and television series are considered, according to Esquenazi’s approach to TV series. Nevertheless, this paper highlights how technical and cultural specificities of today’s digital media, paired with a deep individualization process, set new analytical challenges. So, it is presented an analytical reflection that places together connectivity and cinematic culture in order to comprehend how today’s ideologies are partly influenced by specific recurrent imagistic constructions diffused by streaming platforms by using cinema and television languages.